Pengaruh Job Placement, Beban Kerja, Motivasi, Disiplin dan Organization Culture Terhadap Emplloyee Porformance PT Excelitas Batam - Rosiyanti, Linda; Tibrani; Tamami, Sastra (Lembaga Teewan Journal Solutions, 2026)
This study aims to determine and analyze the influence of job placement, workload, motivation, discipline, and organizational culture on employee performance at PT Excelitas Batam. This study used quantitative methods, and the population was 55 permanent employees at PT Excelitas Batam. The sample used in this study was 55 respondents, using a non-probability sampling technique, namely total sampling. Data were collected through a questionnaire with a Likert scale. Data analysis techniques used included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R2) analysis. The results showed that job placement, workload, motivation, discipline, and organizational culture simultaneously had a significant effect on employee performance at PT. Excelitas Batam. Partially, each independent variable (job placement, workload, motivation, discipline, and organizational culture) also has a positive and significant effect on employee performance.